Effect of Gibberellic Acid (GA3) Concentration and Seedling Media Composition on the Germination and Growth of Shallots (Allium ascalonicum L.) from True Shallot Seed - Nurcharisma, Adinda; Setiyono, Setiyono; Sholikhah, Ummi; Ratnasari, Tri; Savitri, Dyah Ayu; Patricia SM, Susan Barbara; Arum, Ayu Puspita; Novijanto, Noer (International Journal on Food, Agriculture and Natural Resources, 2024)
Shallots (Allium ascalonicum L.) is a vegetable commodity that contributes greatly to horticultural production and inflantion levels. The use of superior seeds is expected to produce maximum shallot production. The majority of Indonesian farmers use 30% of the harvested tubers as planting material, with production costs being quite expensive. Many shallot farmers also experience several problems with tuber seeds that are hollow and damaged. True Shallot Seeds can be an efficient and profitable altervative planting material. Implementing TSS shallot cultivation is considered difficult and requires longer time for sowing. Soaking seeds using Gibberelin can have a physiological effect on the germination process. Seedling media factor with a certain composition are needed to produce maximum seeds. The experiment was carried out in factorial manner using Random Design Complete  with three replications. The GA3 concentration factor has four treatment levels: G0 = 0 ppm/control, G1 = 2 ppm, G2 = 4 ppm, and G3 = 6 ppm. The seedling media composition factors has four treatment levels: M0 = soil + compost/control (1:1), M1 = cocopeat + compost (1:1), M2 = husk charcoal + compost (1:1), and M3 = sand + compost (1:1). The data analysis used was Analysis of Variance, if there were significant differences between the treatments, a further tes was carried out using Duncan’s Multiple Range Test at the 5% level. The result showed that the interaction between GA3 concentration treatment and seedling media composition and the single factor GA3 concentration had no significant effect on all observed variables. The composition of the seedling media has a significant effect on the speed of seed growth, seed height, root length, and seed wet weight with optimum results for germination and vegetative growth of TSS seeds, namely the compositionof soil+compost/control (M0) seedling media on the variables of seed growth speed (%/etmal), seed height (cm), and seed wet weight (gram).